Enterprise Resource Planning (ERP) Implementation in Pakistani Enterprises: Critical Success Factors and Challenges - Muhammad Yousaf Jamil; Rafia Qayyum (Journal of Management and Research, 2015)
ERP systems are the backbone of global supply chain, while their success and failure determines the fate of the business. With enormous competition and ever increasing challenges in boundless trading, the IT linkages and E-Business involve extensive customization. There are many researches on the implementation facilitators and barriers in all types of organizations throughout the world but limited literature can be found in work specific to Pakistan. This study brings out the critical factors that drive a successful ERP system in Pakistan and also discusses the pitfalls to be avoided in order to prevent a disaster. Through this study, the critical success factors and the main challenges for implementation of ERP in Pakistani organizations have been recognized. In this way, suggested to localize for ERP implementation in Pakistani organizations.